2012
DOI: 10.2337/dc12-0028
|View full text |Cite
|
Sign up to set email alerts
|

A 25-Year Longitudinal Evaluation of Gastric Emptying in Diabetes

Abstract: OBJECTIVETo evaluate the natural history of gastric emptying in diabetes.RESEARCH DESIGN AND METHODSThirteen patients with diabetes (12, type 1; 1, type 2) had measurements of gastric emptying, blood glucose levels, glycated hemoglobin, upper gastrointestinal symptoms, and autonomic nerve function at baseline and after 24.7 ± 1.5 years.RESULTSThere was no change in gastric emptying of either solids (% retention at 100 min) (baseline 58.5 ± 5% vs. follow-up 51.9 ± 8%; P = 0.35) or liquids (50% emptying time) (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…From a group of 86 patients assessed at a tertiary referral center, 20 patients, of whom 16 had type 1 DM, were reevaluated 12 years later and only 13 patients (12 had type 1 DM) were reevaluated approximately 25 years after the first study. 23, 29 While gastric emptying was not significantly different 25 years after the baseline assessment, correlation between initial and subsequent assessments was limited, as evidenced by a correlation coefficient of 0.56. 23 …”
Section: Natural History and Outcomesmentioning
confidence: 94%
“…From a group of 86 patients assessed at a tertiary referral center, 20 patients, of whom 16 had type 1 DM, were reevaluated 12 years later and only 13 patients (12 had type 1 DM) were reevaluated approximately 25 years after the first study. 23, 29 While gastric emptying was not significantly different 25 years after the baseline assessment, correlation between initial and subsequent assessments was limited, as evidenced by a correlation coefficient of 0.56. 23 …”
Section: Natural History and Outcomesmentioning
confidence: 94%
“…Beginning with a cohort of 86 patients, 20 patients, of which 16 had type 1 DM, were reassessed 12 years later and 13 patients (12 had type 1 DM) were reassessed approximately 25 years after the first study. 14, 15 Despite a reduction in HbA1c, which was statistically significant at the earlier follow-up point (i.e., 8.4±2.3% at baseline, 7.6±1.3% at 12 years median), GE was stable over time when assessed for the entire group. Hence, the impact of improving control of glycemia on GE in type 2 DM is incompletely understood.…”
Section: Introductionmentioning
confidence: 92%
“…We have reported stability of gastric emptying over two decades in an unselected group of patients with predominantly T1DM. 35 Longitudinal evaluation of large cohorts of patients with diabetes mellitus who also have gastroparesis revealed no association between gastro paresis and increased poor prognosis; 36,37 although this lack of association might not apply to patients with severely delayed gastric emptying. Contrary to our data, another research group reported decreased overall survival in patients with gastroparesis compared with age-matched and sex-matched control individuals in a communitybased study.…”
Section: Natural Historymentioning
confidence: 98%
“…28,29 By contrast, the intra individual variation of gastric emptying is modest. 35,61 Among patients with T1DM, those with gastroparesis have a reduction in early postprandial insulin requirement compared with those with a normal rate of gastric emptying, 62 whereas in intervention studies in patients with T2DM inhibition of gastric emptying by opiates resulted in a marked decrease in glycaemic excursions. 63 However, following administration of the prokinetic erythromycin to patients with T2DM the opposite effects were observed.…”
Section: Gastric Emptying and Glycaemiamentioning
confidence: 98%